Psychometric properties of the Malay-version Police Stress Questionnaire - Rasdi, Irniza; Zainal Abidin, Emilia; Muhammad Saliluddin, Suhainizam; Isha, Ahmad Shahrul Nizam (Universiti Sains Malaysia Press, 2014)
Background: Police Stress Questionnaire (PSQ) was developed to measure police-specific stressors. The present study was the first to have translated the PSQ to Malay. This study aims to test the reliability, construct validity, and component structure of the Malay-version PSQ. Method: A set of survey consisted of the Malay-version PSQ, General Health Questionnaire (GHQ-12), Job Content Questionnaire (JCQ), Global Stress Questionnaire (GSQ) and General Self-rated Health (GSRH) were distributed to 300 traffic police officers in Kuala Lumpur and all traffic police officers in a few districts of Pahang and Negeri Sembilan. Results: The response rate was 65.5% (N = 262). The reported Cronbach’s alpha coefficient was 0.93 for Operational PSQ (PSQ-Op) and 0.94 for Organisational PSQ (PSQ-Org). Findings indicated that the PSQ had positive construct validity with the GSRH, GSQ, and GHQ. After excluding four factors related to lifestyles, all police-specific stressors were highly loaded (0.50) in one component. Conclusion: It is confirmed that the Malay-version PSQ, excluding the four factors related to lifestyle, was uni-dimensional, reliable, and a valid questionnaire. This study proffers a potentially better instrument for assessing the stressors among Malaysian police.